1977
DOI: 10.1007/bf01906355
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial function in different models of cardiac hypertrophy. An attempt at correlating mechanical, biochemical, and morphological parameters

Abstract: Based on mechanical, biochemical and electron microscopic studies performed in the same stage of experimental cardiac hypertrophy, an attempt is made to define the significance of individual factors responsible for the alterations in myocardial function. Using swimming rats, it is demonstrated that a load-induced increase in cardiac mass is not necessarily connected with an impairment of contractile capability on a cellular level. Yet, also, the reduction of specific ATPase activity and unloaded shortening vel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1980
1980
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…in left ventricular tissue of Goldblatt rats at an early stage (up to 6 weeks after surgery) is to be expected in different experimental groups. Our previous study [11] demonstrated that ventricular contractile capability can be increased in this phase of cardiac hypertrophy, as an expression of adaptation to increased functional requirements.…”
Section: Discussionmentioning
confidence: 98%
“…in left ventricular tissue of Goldblatt rats at an early stage (up to 6 weeks after surgery) is to be expected in different experimental groups. Our previous study [11] demonstrated that ventricular contractile capability can be increased in this phase of cardiac hypertrophy, as an expression of adaptation to increased functional requirements.…”
Section: Discussionmentioning
confidence: 98%
“…This report confirms that Tables I and II. cardiac hypertrophy due to renal hypertension in rats is associated with a depressed coronary reserve (7,17) and diminished contractile performance ofthe left ventricle (4)(5)(6)(7). These results contrast with our previous findings ofimproved contractile performance in hypertrophied hearts from female rats trained by a chronic swimming program (12).…”
Section: Discussionmentioning
confidence: 80%
“…Half of the animals in the control and hypertensive groups were subjected to a swimming program and the other half remained cage-confined (sedentary). The exercise program, described previously (1 1-13), consisted of swimming 5 d/wk, 75 min twice a day for 10 wk. At the completion of this period, exercised and sedentary animals were anesthetized with ether, their hearts were removed and studied in the isolated working rat heart apparatus.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations